Temporal Drivers of Liking. (March 2015) - Thomas, Arnaud; Visalli, Michel; Cordelle, Sylvie; Schlich, Pascal
Highlights: A new technique mixing TDS and liking tests with untrained consumers. Allowing to suggest the sequence of attributes which would drive preference. Repeated liking tests over consumption is more discriminative than classic liking. Usual liking scores may be given too quickly by consumers. Abstract: Generally liking is measured overall but is likely to vary over the food intake, like sensory perception. Replacing the attributes in Temporal Dominance of Sensations (TDS) by the categories of a usual ordinal liking scale makes it possible to monitor liking changes while eating a product (Sudre et al., 2012). This methodology allows for a better understanding of the influence of temporal dominance of sensations on liking and liking evolution over the time of product intake. Thus, it is possible to associate hedonic temporal data and descriptive temporal data (TDS profiles), which would identify drivers of liking, that is attributes which, when cited as dominant, would lead to a decrease or an increase of liking. Sixty-eight French consumers participated in four lab sessions. During the 1st session, the subjects had to taste six flavored fresh cheeses and to indicate their overall liking for each product. Temporal liking of the same products was evaluated throughout the tasting in the 2nd session. The 3rd session was a measure of TDS for the same products and only dominance was recorded (no intensity recorded). Finally, in the 4th session, the measure of liking of the same products was recorded 1 min after the beginning of tasting of each sample. Measures of liking showed that temporal liking is more discriminative than classic liking, and that classic liking scores may have been given before swallowing. However, waiting for 1 min before asking a liking score decreases discrimination of the products. Furthermore, combining temporal liking and TDS data obtained from the same consumers allowed to suggest the attributes and the times to which the perception of those attributes is responsible for the liking or disliking of the product. This is a new concept of "positive or negative Temporal Drivers of Liking" (TDL). The paper proposes to compute individual average liking scores while a given attribute was perceived as dominant (LWD) and to average those LWD values over the subject for extracting the TDLs of a specific product or of a group of products.